2016
DOI: 10.1038/srep39299
|View full text |Cite
|
Sign up to set email alerts
|

Huangqin-tang ameliorates dextran sodium sulphate-induced colitis by regulating intestinal epithelial cell homeostasis, inflammation and immune response

Abstract: Huangqin-tang (HQT) is a traditional Chinese medicine (TCM) formula widely used for the treatment of inflammatory bowel disease in China. However, the molecular mechanisms by which HQT protects the colon are unclear. We studied the protective effects of HQT and the underlying mechanisms in an experimental mouse model and in vitro. In vivo, dextran sodium sulphate (DSS)-induced acute and chronic colitis were significantly ameliorated by HQT as gauged by phenotypic, histopathologic and inflammatory manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 48 publications
2
24
0
Order By: Relevance
“…The acute DSS model is implemented over 1–2 weeks and is used to achieve short-term alterations in the intestinal barrier, whereas the chronic DSS mouse model is implemented over a period of 2–4 months to cause long-term effects on intestinal immunity and damage, serving as an effective model for chronic colitis (Wirtz et al, 2017). Because genetic factors for IBD are currently not well-established and only account for a portion of IBD, with one study finding that only 12% of UC patients have a familial history of IBD (Zhang and Li, 2014; Childers et al, 2014), the chronic DSS mouse model is particularly appropriate to model IBDs triggered by environmental factors (Schippers et al, 2016; Hoffmann et al, 2017; Zou et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The acute DSS model is implemented over 1–2 weeks and is used to achieve short-term alterations in the intestinal barrier, whereas the chronic DSS mouse model is implemented over a period of 2–4 months to cause long-term effects on intestinal immunity and damage, serving as an effective model for chronic colitis (Wirtz et al, 2017). Because genetic factors for IBD are currently not well-established and only account for a portion of IBD, with one study finding that only 12% of UC patients have a familial history of IBD (Zhang and Li, 2014; Childers et al, 2014), the chronic DSS mouse model is particularly appropriate to model IBDs triggered by environmental factors (Schippers et al, 2016; Hoffmann et al, 2017; Zou et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Histologic scoring was performed by an investigator blinded to the project based on previously described criteria [ 15 ]. 0 = normal; 1 = moderate mucosal inflammation without erosion and ulcer; 2 = severe mucosal inflammation with erosion; 3 = severe mucosal inflammation with ulcer (< 1 mm); 4 = severe mucosal inflammation with ulcer (1–3 mm); 5 = severe mucosal inflammation with ulcer (> 3 mm).…”
Section: Methodsmentioning
confidence: 99%
“…(jujube, 49 g). Recent studies showed that HQD alleviated inflammation through suppression of the nuclear factor-kappa B (NF-kB) pathway and regulation of the gut microbiota to improve the intestinal microenvironment in mouse models of dextran sulfate sodium (DSS)-induced UC (Chen et al, 2016;Zou et al, 2016;Yang et al, 2017). However, these studies did not clarify how the gut microbiota exerted effects on inflammatory pathways.…”
Section: Introductionmentioning
confidence: 99%